Understanding the association of calligraphy activities with flow experience, peace of mind, and self-focused attention among university students - Jianing Wang; Kaizhi Tang (Frontiers in Psychology)
IntroductionCalligraphy, as a mindful practice, fosters focus, creativity, and relaxation, all of which contribute to a more peaceful mental state. For university students, regular engagement in calligraphy can help develop better coping mechanisms for academic and personal stress. This enhanced ability to manage stress can lead to improved mental well-being, greater self-awareness, and a more positive outlook, supporting their overall academic and personal development.MethodsThis study employed convenience sampling and snowball sampling to select 453 university students from Hunan Province, China, in September 2024 as valid samples. AMOS v.23 was used to construct a structural equation model to validate the hypotheses.ResultsThe study revealed a significant positive relationship between calligraphy activities and both flow experience and peace of mind. Furthermore, a strong positive correlation was observed between flow experience, peace of mind, and self-focused attention. In addition, flow experience and peace of mind were found to mediate the relationship between calligraphy activities and self-focused attention.DiscussionThe findings highlight the positive role of calligraphy activities in enhancing university students’ mental well-being, particularly through promoting flow experience and peace of mind. These factors not only directly benefit self-focused attention but also serve as mediators, suggesting that calligraphy can be an effective intervention for improving concentration and emotional balance. This study underscores the potential of incorporating calligraphy into student wellness programs to support both academic performance and personal development.